2014
DOI: 10.4161/hv.28299
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses induced by T-cell vaccination in patients with rheumatoid arthritis

Abstract: Patients with rheumatoid arthritis (RA) were treated with a cellular vaccine, which consisted of autologous collagen-reactive T-cells. This study showed that antigen-specific proliferative activity of the peripheral blood mononuclear cells was significantly downregulated after T-cell vaccination in RA patients. T-cell vaccination resulted in a statistically significant decrease in plasma IFNγ levels and a concomitant increase in IL-4 levels in treated patients. Accordingly, following T-cell vaccination the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…No apparent side effects were observed during the treatment and follow-up period, so we assumed attenuated T cell vaccination is safe in use for SLE, which accords with previous studies [15, 17, 18, 34]. …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…No apparent side effects were observed during the treatment and follow-up period, so we assumed attenuated T cell vaccination is safe in use for SLE, which accords with previous studies [15, 17, 18, 34]. …”
Section: Discussionsupporting
confidence: 86%
“…Attenuated T cells are believed to alleviate manifestation of autoimmune diseases through clearing pathogenic autoreactive T cells [13, 18]. The study supported this idea because antiautoreactive T cell antibodies were observed in W4 and increased in W8, which concurred with the fact that most patients' clinical manifestations were relieved in W4 and were evidently improved in W8, including decreasing SLEDAI and remissions on various clinical features, such as facial rash, low complementemia, and proteinuria.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…12 A more recent study on vaccination with collagen II reactive T cells in RA showed a favorable immunological effect with raised levels of activated Foxp-3+ Treg's. 13 Another study with a significant clinical effect of T cell vaccination was carried out with irradiated myelin basic protein (MBP) specific T cells in patients with progressive multiple sclerosis (MS). 14 Along similar lines, my group had carried out some underpinning research on T-T cell interactions the rat model.…”
Section: Therapeutic Tolerancementioning
confidence: 99%
“…We have developed a two-step technology of T-cell vaccine preparation that is technically straightforward, and does not include long-lasting cell culturing procedures making it easily reproducible under the GMP conditions (Ivanova et al 2005(Ivanova et al , 2008(Ivanova et al , 2014. Myelin has been isolated from porcine brain as described previously (Deibler et al 1972).…”
Section: T-cell Vaccine Preparationmentioning
confidence: 99%